Feasibility study for the reuse of a fixed offshore platform as a substructure for wind towers (Research, Society and Development, 2020)
In order to give another use to fixed offshore platforms with expired useful life, especially those located in fields with favorable environmental conditions for installing offshore wind turbines, the present research highlights the importance of evaluating the possibility of reuse of a platform (jacket) subjected to the loading of a 10 MW towers, especially considering the new operating conditions. For this, the analysis of the elements that make up the structure (jacket) is taken into account in order to adjust their respective stress ratios. The loading of the wind tower was considered to be punctually distributed over the 4 knots at the top of the main legs of the jacket. The investigated structure features a 16.85 m high jacket, with the bottom table area of 9.95 m x 9.95 m and 6.75 m x 6.75 m on the upper table. The structural system was developed based on the use of the OrcaFlex V10.3 software, which allows to analyze the stress ratios (“Unity Check”) including the second order effects using the Finite Element Method (MEF). Thus, the results obtained during the analyzes to assess the structural behavior point to the fact that the jacket investigated does not meet the design criteria to support 10 MW wind towers.